Threshold effects and regional economic growth – Evidence from West Germany - Michael Funke; Annekatrin Niebuhr (Hamburg Institute of International Economics (HWWA), 2001)
We study an overlapping generations model of human capital accumulation with threshold effects using regional data for West Germany. Our basic goal is to shed light on the growth of West German regions. The paper finds that the relative income distribution appears to be stratifying into a trimodal distribution. Thus, application of the threshold model to a real world case, here West Germany, shows that the model might help to explain regional growth patterns. – – Ausgangspunkt der Analyse ist ein Modell überlappender Generationen der Humankapitalakkumulation mit Schwellenwert-Effekten. Die empirische Überprüfung des Modells basiert auf einem regionalen Datensatz für Westdeutschland. Das zentrale Ziel der Untersuchung ist es, Erkenntnisse zum Wachstum westdeutscher Regionen zu liefern. Den Ergebnisse der empirischen Analyse zufolge ist die relative Einkommensverteilung der westdeutschen Regionen durch eine Aufgliederung in drei unterschiedliche Konvergenzclubs gekennzeichnet. Die Resultate weisen darauf hin, dass das Schwellenwert-Modell zur Erklärung regionaler Wachstumsprozesse beitragen kann.
Keywords: R11; O40; C31; J24; 330; Regional Economic Growth; Human Capital; Germany; Regionales Wachstum; Bildungsinvestition; Entwicklungskonvergenz; Regionale Wachstumstheorie; Overlapping Generations; Alte Bundesländer; Deutschland; Schwellenwert